EFFECT OF EDUCATION WITH THE METHOD AND VIDEO ANIMATION ON BALANCED NUTRITION KNOWLEDGE FOR PREVENTION ANEMIA - Miratul Haya; Tetes Wahyu (Universitas Bengkulu, 2021)
The prevalence of anemia among adolescent girls in Bengkulu city is very high, reaching 43%. The Indonesian Ministry of Health (2018) states that anemia in adolescent girls is a health problem if the prevalence is ?20%, so it is necessary to carry out further research to find out the main problem of anemia in young women in the city of Bengkulu.to determine the effect of nutrition education with lecture methods and animated videos on knowledge of balanced nutrition for the prevention of anemia in adolescents in SMA N 9 Bengkulu City in 2021.This type of quasy experimental design with Two group pre-test post test design. The student population is 175 people, with a sample size of 40 people. Data analysis using independent t-test and dependent t-test.Knowledge of young women before and after being given education with the lecture method with a p-value of 0.0005, then the p-value (<0.05), and the knowledge of young women before and after being given education using the video animation method with a p-value. value 0.0005 then the p-value (<0.05).There is an effect of nutrition education with lecture methods and animated videos on balanced nutrition knowledge to prevent adolescent anemia in SMA N 9 Bengkulu City in 2021. It is hoped that young women who have received nutrition education can maintain their knowledge to be able to change attitudes and actions true related to balanced nutrition in everyday life in order to prevent anemia.